Analysis Of The Effect Of Halal Labels And Brand Image On The Decision To Purchase Ms Glow Products In Mataram City - Farhatunnisah Farhatunnisah; Diah Lukitasari; Ira Dianti (Business Management, 2026)
This study aims to determine the effect of Halal Label and Brand Image on Purchasing Decisions of MS Glow Products in Mataram City. This study uses a quantitative approach with descriptive methods. The research sample consisted of 97 respondents who use MS Glow Products in Mataram City. with the purposive sampling technique. Data analysis was carried out using multiple linear regression with the help of SPSS version 27. The results of the study indicate that a partially Halal Label does not have a positive and significant effect on Purchasing Decisions with a calculated t value <t table and a significance value of 0.154> 0.05. While Brand Image has a positive and significant effect on Purchasing Decisions, with a significance value of <0.001 <0.05. Furthermore, Simultaneously, Halal Label and Brand Image have a significant effect on Purchasing Decisions with a calculated F value> F table and a significance value of <0.001 <0.05. The results of the determination coefficient test show an R-Square value of ±0.6, which means that Halal Labels and Brand Image are able to explain around 60% of the variation in Purchasing Decisions, while the rest is influenced by other variables outside this study.